2022
DOI: 10.1186/s13195-022-01003-w
|View full text |Cite
|
Sign up to set email alerts
|

The cerebrospinal fluid biomarker ratio Aβ42/40 identifies amyloid positron emission tomography positivity better than Aβ42 alone in a heterogeneous memory clinic cohort

Abstract: Background Cerebrospinal fluid (CSF) analysis for detecting amyloid positivity may be as reliable as positron emission tomography (PET). We evaluated the performance of the amyloid beta (Aβ)42/40 ratio for predicting amyloid positivity by PET, compared with Aβ42 alone, and phosphorylated tau 181 (pTau181)/Aβ42 and total tau (tTau)/Aβ42 ratios, using fully automated CSF immunoassays (Roche Diagnostics International Ltd, Rotkreuz, Switzerland) in a heterogeneous cohort of patients with a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
(52 reference statements)
0
15
1
Order By: Relevance
“…In another study, mouse neuroblastoma cells with this L238F variant had an increased Aβ42/40 ratio compared to wildtype cells which led to the classification for this variant as “probable pathogenic” (Hsu et al 2020). An increased Aβ42/40 ratio is a predictor of amyloid-PET positivity in patients with Alzheimer’s disease (Amft et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, mouse neuroblastoma cells with this L238F variant had an increased Aβ42/40 ratio compared to wildtype cells which led to the classification for this variant as “probable pathogenic” (Hsu et al 2020). An increased Aβ42/40 ratio is a predictor of amyloid-PET positivity in patients with Alzheimer’s disease (Amft et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…We assessed plasma Aβ 42 /Aβ 40 as a measure of amyloid consistently with previous studies reporting that this measure identifies amyloid deposition better than Aβ 42 alone 10. Moreover, we considered plasma p-tau/Aβ 42 as a measure of both amyloid and tau as previous studies suggested that this measure is predictive of both amyloid10 11 and tau12 deposition.…”
Section: Methodsmentioning
confidence: 99%
“…CSF Aβ42 and the Aβ42/40 ratio decrease early in AD and are negatively correlated with amyloid PET [14] and amyloid plaques presence, a hallmark neuropathology of AD [15]. CSF Aβ42/40 ratio has been reported to predict PET amyloid-positivity more accurately than CSF Aβ42 alone, regardless of clinical diagnosis [16,17]. Another key pathological hallmark of AD, neurofibrillary tangles composed of hyperphosphorylated tau, is positively correlated with CSF ptau181 concentration [18].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%